Minimum hydrogen consumption power allocation strategy for the multi-stack fuel cell (MFC) system based on a discrete approach - Liang, YiFan; Liang, QianChao; Zhao, JianFeng; He, JunNeng (Frontiers in Energy Research, 2022)
A minimum hydrogen consumption power allocation strategy based on discrete data is proposed to ensure that the multi-stack fuel cell system (MFC system) operates with minimum hydrogen consumption in response to external load demand. This strategy is developed by processing the discrete data of single-stack fuel cell hydrogen consumption with the dynamic programming inverse derivation. And it classified the approach by activated state. During system operation, the Power of the MFC system is controlled online by checking the table. System validation is performed by modeling the system in Simulink based on fuel cell operation data. It shows that the proposed strategy has less hydrogen consumption than average, the Daisy-Chain strategy, and the real-time power distribution to the MFC system.